Matrix reloaded [videorecording (DVD)] - Silver, Joel; Wachowski, Lilly, 1967-; Wachowski, Lana, 1965-; Fishburne, Laurence, III, 1961-; Reeves, Keanu; Moss, Carrie-Anne, 1970- (Warner Home Video, 2003)
Neo, Trinity, and Morpheus continue to lead the revolt against the Machine Army. In their quest to save the human race from extinction, they gain greater insight into the construction of The Matrix and Neo's pivotal role in the fate of mankind.